Education Between Entertainment and Training: An Applied Study on Public Schools in Mahayel Asir Province - Al-Habiri, Layla Ahmed (Journal of Educational and Psychological Sciences, 2024)
The research aimed to explore the relationship between education, training, and entertainment within the fields of education and development. It also sought to highlight the positive role of implementing recreational activities in education and training for all age groups, with activities tailored to each specific age group. The study utilized a descriptive-analytical methodology, applied across 15 schools encompassing three educational levels (elementary, middle, and high school). The sample consisted of one class from each school, comprising 20 students per class, totaling 300 students. Several tools were used, including: (1) special forms for learning resource center supervisors and subject teachers, filled in by observing students during activities conducted in the learning resource centers, (2) electronic questionnaires distributed via WhatsApp to be completed by the educational and administrative staff of the schools, and (3) personal interviews with some students and teachers to assess the effectiveness of the study’s applications and to complete the questionnaires within the school environment, The study revealed that 50% of the students showed a low level of performance due to the lack of internal motivation and readiness for learning prior to the educational stage. On the other hand, the results indicated that 67% of the students improved their performance during classes due to simple recreational activities before the lesson, as this type of entertainment ignited enthusiasm and readiness for learning. Additionally, it was found that training played a role in enhancing students' skills by 78%. Based on these findings, the researcher recommended paying close attention to learners' motivation, carefully selecting recreational activities to align with lesson objectives, establishing precise standards to evaluate the success and quality of the educational process, identifying students' strengths and weaknesses, and focusing on unmastered skills through intensive training.
Keywords: Education; Entertainment; Training